Circularidad cognitiva en la filosofía Sāmkhya - Arnau, Juan (THÉMATA. Revista de Filosofía, 2013)
El artículo se dedica al análisis de las teorías cognitivas y la hermenéutica de la filosofía sāmkhya, uno de los seis sistemas ortodoxos de la tradición brahmánica. Para ello se utilizan como fuentes primarias dos textos sánscritos: la Sāmkhyakārikā (s. IV) y el Tattvakaumudī (s. IX). Tras una breve introducción, se analizan los componentes del mundo físico según el sāmkhya, la circularidad cognitiva en un mundo hecho de sensaciones, los problemas epistemológicos que esto plantea y algunas cuestiones acerca de la naturaleza de la conciencia. The article is dedicated to the analysis of the cognitive theories and hermeneutics of the Sāmkhya philosophical System, one of the six Orthodox systems of the Brahmanical tradition. For this purpose two Sanskrit texts are used as primary sources: the Sāmkhyakārikā (s. IV) and the Tattvakaumudī (s. IX). After a brief introduction, the article discusses the components of the physical world according to the sāmkhya, the cognitive circularity in a world made up of sensations, the epistemological problems posed by this and some issues about the nature of consciousness.